MEANING IN LIFE DAN KONSEKUENSINYA: STUDI PADA STAF PENGAJAR UNIVERSITAS JENDERAL SOEDIRMAN - Sri Lestari (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2014)
Study on meaning, or widely known as meaning in life commonly studied from the perspective of existential psychology. Meaning is an important construct since meaning will help individual in seeking and finding the goals of individual existence. Previous studies show that meaning is utilized in two context, life meaning and job meaning. We argue that the two constructs is closely related so that in some studies, both terms ussually interchangeably used.The aim of the research is to investigate the consequences of meaning in life. Field survey is conducted in Universitas Jenderal Soedirman with the sample size of 140 lecturers. The findings are as follows: meaning in life significantly influence job involvement and lecturer motivation, job involvement significantly influence career planning, but insignificantly toward career identity, whereas motivation significantly influence career identity and career planning. The future research could be conducted to verify current finding, particularly to validate the influence of job involvement toward career identity.